PENYULUHAN DAN PRAKTEK TENTANG PERILAKU HIDUP BERSIH DAN SEHAT DI SD INPRES LARIANG BANGI: - - -, Firawati; Hartih, Nuraeni; Hasrida, Hasrida (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Clean and Healthy Living Behavior (PHBS) in schools is a set of behaviors that are practiced by students, teachers, and the school community on the basis of awareness as learning outcomes, so that they are able to independently prevent disease, improve their health, and play an active role in creating a healthy environment. Community service in the form of counseling is carried out at SD Inpres Lariang Bangi with a community development method. The results obtained were in the form of enthusiasm from the counseling participants, the availability of hand washing and trash bins, and the need to increase the habituation of daily PHBS practices.